Bez rozglosu - Lindsey, David L.; Pyka, Jan. (Poznan : REBIS, 2004)
Polish translation of "Rules of silence". Titus Cain is a bilionaire who is subjected to an extortion plot by Cayetane Loquin.
Keywords: Kidnapping victims -- Fiction; Billionaires -- Fiction; Extortion -- Fiction; Criminals -- Fiction; Texas -- Fiction